Is Pakistan ready to implement Artificial Intelligence? - Hamna Tariq,; Areeba Sajid, (Journal of the Pakistan Medical Association, 2023)
Madam, The phrase "artificial intelligence" (AI) refers to the capacity of computers to accomplish activities that humans can typically performed by utilising an Artificial Neural Network (ANN) (1). The Artificial intelligence has become an exceptionally desirable analytical tool in medicine due to its ability to generalise, handle imprecise information, analyse non-linear data, and learn from historical precedents (2). According to Tata Consultancy Services Global Trends Study focusing on artificial intelligence and its impact on the healthcare industry, 86% of healthcare companies use AI", indicating its significance in improving healthcare (3). AI is employed everywhere, ensuring accuracy and speed in every aspect of a patient's diagnosis to their prognosis and treatment, revolutionising medicine (4) Despite all the benefits of AI, multiple factors need to be kept in mind before it can be successfully applied. AI works on software that is designed in accordance with data sets. If the data used in programming is not diverse, it will inevitably result in prejudice worsening the discriminatory outcomes in healthcare. There are numerous examples of AI being biased. For example, gender discrimination was a problem with facial recognition algorithms developed by Microsoft, IBM, and Face++; these AI systems were better at identifying the gender of white males than those with a darker complexion (5). When an advanced company like Amazon faces such issues, do we think a developing country like Pakistan will be equipped to successfully implement AI in a vast field like medicine? In Pakistan, women are typically responsible for the care of the home and are restricted in their capacity to travel alone and prioritise the health of their male family members (6). So will women be able to contribute their confidential information for AI data sets while they are confined to their houses? This could result in data that is weighted towards men (6). Conducting surveys is a crucial part of data collection (7). We must be cognizant that not all of Pakistan is accessible and that people there have a variety of objections and obstinate attitudes (7). The most recent COVID-19 outbreak was the ideal illustration of their ignorant behaviour (7). This demonstrates how unlikely it is to obtain data from the Pakistani population, which means only limited data can be collected. Since AI data sets heavily rely on Volume, variety and velocity so it is natural for AI not to prevail in Pakistan (7). ---Continue